Characterization of capillary pressure–saturation relationships for double-porosity medium using light transmission visualization technique - Alazaiza, Motasem Y. D.; Copty, Nadim K.; Ngien, S. K.; Bob, Mustafa M.; Aburas, Maher M. (Springer International Publishing, 2019)
Capillary pressure saturation (Pc–Sw) relationship plays a central role in the description of fluid flow in porous media. In this research, the light transmission visualization (LTV) technique was applied to characterize the Pc–Sw relationship in a double-porosity medium. Four experiments were conducted in two-dimensional (2-D) flow chambers packed with a double-porosity medium composed of a mixture of silica sand and sintered kaolin clay spheres. In each experiment, a different volumetric fraction of macropores and micropores was used. The experiment was also repeated by compacting the flow chamber with silica sand only to represent single-porosity medium. Variable saturations of water across the height of the system were applied by controlling the capillary pressure. Images of the 2-D model were collected using a digital camera and analyzed pixel by pixel to determine water saturation in the double-porosity medium. Results from the LTV technique showed that the Pc–Sw relationships for all experiments in double-porosity soil medium were similar in shape but varied depending on the porous media composition. Comparison with the pressure cell test results showed that the Pc–Sw curves for all experiments consistent comparable to those obtained by the LTV technique. The Pc–Sw curves were also fit to van Genuchten model for comparison and validation. For double-porosity media, the best-fit parameters were consistent with published data for sandy clay. Moreover, little variability was observed in the best-fit α and n values for the different double porosity. Overall, this study proves that the LTV technique is a noninvasive laboratory tool that can provide high-resolution spatial data for water saturation distribution in different types of porous media and is capable of producing highly resolved Pc–Sw relationships.